2021
DOI: 10.1111/jcmm.16779
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant platelet‐derived growth factor‐BB alleviates osteoarthritis in a rat model by decreasing chondrocyte apoptosis in vitro and in vivo

Abstract: Osteoarthritis (OA) is a common joint disease that mainly affects the diarthrodial joints. Treatments for OA include non‐pharmacological interventions, topical and oral therapies, intra‐articular therapies and joint surgery. However, all the treatments mentioned above mainly aim to control the symptoms instead of improving or reversing the joint condition. In this research, we observed the effect of recombinant platelet‐derived growth factor (PDGF)‐BB on OA in a monosodium iodoacetate (MIA)–induced rat model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…The phosphorylation cascade process is initiated by this binding, which eventually results in the activation of ERK. ERK activation may inhibit apoptosis by phosphorylating and deactivating proteins that promote apoptosis or by controlling the production of proteins that inhibit apoptosis [17,[47][48][49]. In the P38 signaling pathway, PDGF-BB has the ability to decrease the activity of p38, resulting in a decrease in BAX protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphorylation cascade process is initiated by this binding, which eventually results in the activation of ERK. ERK activation may inhibit apoptosis by phosphorylating and deactivating proteins that promote apoptosis or by controlling the production of proteins that inhibit apoptosis [17,[47][48][49]. In the P38 signaling pathway, PDGF-BB has the ability to decrease the activity of p38, resulting in a decrease in BAX protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Med. 2024, 14, x FOR PEER REVIEW 9 of 13 of proteins that inhibit apoptosis [17,[47][48][49]. In the P38 signaling pathway, PDGF-BB has the ability to decrease the activity of p38, resulting in a decrease in BAX protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…HA hydrogels loaded with rhPDGF-BB have shown significant improvement of the anabolism of collagen type II and inhibition of the catabolism of chondrocytes in a rat knee OA model [ 404 ]. Meanwhile, rhPDGF-BB could be used to alleviate the level of inflammation in chondrocytes and decrease the apoptosis rate of chondrocytes [ 405 ]. It has also been demonstrated that collagen sponge impregnated with PDGF was able to repair full-thickness osteochondral defect of New Zealand while rabbits [ 406 ].…”
Section: Cell Sources and Growth Factors In Mzssmentioning
confidence: 99%
“…It improves the anabolism of collagen type II and inhibition of the catabolism of chondrocytes, and it also alleviates inflammation in chondrocytes and decreases chondrocytes apoptosis. [ 401 , 402 , 404 , 405 ] PDGF-AA/AB/BB BL/CL Commercially available PDGFs are usually a mix of all three isoforms of PDGFs that have shown to repair full thickness of OC defects. [ 406 , 407 ] IGFs associated with a series of life-threaten diseases; the main anabolic GF for articular cartilage and play important role in cartilage homeostasis IGF1 BL/CL Its decrease is associated with increased risk of rheumatoid arthritis.…”
Section: Cell Sources and Growth Factors In Mzssmentioning
confidence: 99%
“…PDGF is a growth factor known for its beneficial properties in healing wounds by affecting chemotaxis, angiogenesis and cell mitosis [ 104 ]. It has also been established that PDGF inhibits inflammatory processes and apoptosis in in vitro models by reducing the expression of apoptotic proteins protein 38 (p38), BCL2 Associated X (Bax) and caspase-3 with a parallel increase in the expression of the protein responsible for cell survival, ERK [ 105 ]. In chondrogenesis it increases the level of type II collagen that builds cartilage, reduces the level of collagen X in hypertrophic chondrocytes and alleviates cartilage hyperplasia [ 105 ].…”
Section: Composition Of Conditioned Mediamentioning
confidence: 99%